Pengaruh Harga Palm Oil (CPO) dan Nilai Tukar Rupiah terhadap Return Saham Perusahaan Perkebunan yang Terdaftar di BEI 2020 – 2024 - Safrida Safrida; Muzakir Muzakir; Abu Hasan Makmum (Indo Publishing, 2026)
This study analyzes the effect of global crude palm oil (CPO) prices and the Indonesian Rupiah (IDR) exchange rate on the stock returns of IDX-listed plantation companies from 2020 to 2024. As a strategic sector in Indonesia's economy, the palm oil industry's performance and investor returns are highly susceptible to these macroeconomic fluctuations. Employing a quantitative approach, this research utilizes secondary data from the IDX, Bank Indonesia, and global CPO indices. Through purposive sampling, 15 companies were selected, yielding 75 observations. Data were analyzed using multiple linear regression, preceded by descriptive statistics and classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). The findings aim to provide empirical evidence on how CPO prices and exchange rates drive stock returns. Ultimately, these results offer crucial insights for investors in making investment decisions, assist company management in shaping financial strategies, and serve as a valuable reference for future academic research on capital markets and macroeconomic variables.